Marriage as A Reward for Disney Princesses - Ivena Ivena (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study focuses on the animations of three Disney princesses which are Snow White, Cinderella, and Aurora. Its goal is to find the meaning of marriage for the princesses that happen in the animations. The theories that are used for this study is the ideology of patriarchy, “Angel in the House” concept, and “Damsel in Distress” concept, which affect the characters in the animations. From the analysis, the marriage means a reward for the trio after they have suffered in order to reach perfection. By following the process according to the rule of patriarchy, the trio manages to become the ideal women and are given reward in the form of marriage. Thus, through their animations, Disney wants to show the audience about the ideology of patriarchy